Scuba diving - Walter, Claire (Camden, Me. : Ragged Mountain Press/McGraw-Hill, 2000)
This guide is written for women and intended to introduce the beginner to the activity of scuba diving.
AcknowledgmentsIntroductionWhat is diving?Who dives?About this bookChapter 1: Women and Scuba DivingA sport for (almost) allThe many faces of scuba divingBut is it exercise?Chapter 2: Getting StartedTesting the watersSigning upAgencies from A (ACSU) to Y (YMCA)What will it cost?ShortcutsDeep-six those fearsReality chases misperceptionsChapter 3: Gear TalkBorrow, rent, or buy?MaskSnorkelBuoyancy compensatorRegulatorTankWeightsFinsExposure protectionChapter 4: Ready, Set, Learn to DiveTune your body for divingWhere to startWhat to expectThe first testChapter 5: Into Open WaterThe humblerRedemptionDive rightBuddy upGetting hookedThe next stepChapter 6: Diving SafelyWhen not to diveWhat can go wrongEmergency!How low can you go?Cover yourselfChapter 7: You're Certified--Now What?Underwater adventuresTechnical divingWater worldTaking certification to a higher levelPassing the torchDiving for creditDiving for dollarsVolunteer opportunitiesChapter 8: The Softer Side of ScubaThe undersea environmentResponsible diving--and diningDream dive tripsSelecting a dive destinationScuba diving clubsFamily activitiesThe bottom line on bottom timeChapter 9: GlossaryChapter 10: ResourcesIndex
Includes bibliographical references (pages 134-135) and index.
Keywords: Scuba diving; Women divers